2015
DOI: 10.1073/pnas.1502074112
|View full text |Cite
|
Sign up to set email alerts
|

Climate-driven diversity loss in a grassland community

Abstract: Local ecological communities represent the scale at which species coexist and share resources, and at which diversity has been experimentally shown to underlie stability, productivity, invasion resistance, and other desirable community properties. Globally, community diversity shows a mixture of increases and decreases over recent decades, and these changes have relatively seldom been linked to climatic trends. In a heterogeneous California grassland, we documented declining plant diversity from 2000 to 2014 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
176
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(194 citation statements)
references
References 45 publications
17
176
1
Order By: Relevance
“…A variety of evidence is consistent with this prediction (29). For example, effects of experimental warming and drought were lower in an infertile limestone grassland than in a fertile ex-cultivated grassland (13,30); post-Pleistocene vegetation change was less pronounced on infertile peridotite than in forests on fertile granitic substrates (31); and in our study system, both experimental watering (25,32) and ambient variation in annual precipitation (33,34) had less effect on grasslands on serpentine soils than on more productive grasslands on sedimentary soils. If these contrasting plant community responses to climate are attributable to colimitation by water and nutrients, then several important implications follow.…”
supporting
confidence: 81%
“…A variety of evidence is consistent with this prediction (29). For example, effects of experimental warming and drought were lower in an infertile limestone grassland than in a fertile ex-cultivated grassland (13,30); post-Pleistocene vegetation change was less pronounced on infertile peridotite than in forests on fertile granitic substrates (31); and in our study system, both experimental watering (25,32) and ambient variation in annual precipitation (33,34) had less effect on grasslands on serpentine soils than on more productive grasslands on sedimentary soils. If these contrasting plant community responses to climate are attributable to colimitation by water and nutrients, then several important implications follow.…”
supporting
confidence: 81%
“…Our dataset allowed us to test the impact of the range of most likely drivers of species loss in this ecosystem, strengthening confidence in our inference (34). These results represent one of the few examples of climatedriven diversity loss in natural communities (1), are the first example from the hyperdiverse flora of the CFR (4), and demonstrate an important interaction between climate change and disturbance by fire that suggests flammable ecosystems, especially those subject to crown fires, may be particularly sensitive to climate change (4,52).…”
Section: Discussionsupporting
confidence: 52%
“…Cape Floristic Region | Fynbos | South Africa | biodiversity | climate change A mid mounting evidence of climate change impacts on living systems (1)(2)(3), there is increasing concern about changing disturbance-climate interactions and their potential impacts on biodiversity and ecosystem function (4)(5)(6)(7)(8)(9). Fire is a ubiquitous driver of disturbance across the globe and is essential for the healthy functioning and maintenance of many ecosystems (10,11), but changes in fire regime or postfire weather may drive major shifts in the composition, structure, and function of ecosystems (12).…”
mentioning
confidence: 99%
“…We also cannot rule out the possibility that responses were contingent on conditions specific to the fire year, although total precipitation immediately after fire (2013–2014) was closer to average than for any other growing season in the study (Figure ). Still, our findings are consistent with declines in both above‐ground cover and seed banks of exotic grasses in other California grasslands during the recent drought, paralleled by increases in some native forbs (Harrison, Gornish, & Copeland, ; LaForgia, Spasojevic, Cse, Latimer, & Harrison, ). Similarly, in a predominately native California grassland the recent drought corresponded with disproportionate declines of the most common species and compensatory increases in some rarer competitors (Prugh et al, ).…”
Section: Discussionsupporting
confidence: 86%
“…Other recent research similarly suggests that species‐specific responses to abiotic stress and disturbance are more important than broad differences between invasive and native species (Funk & Zachary, ). Encouragingly, species trait‐based approaches show promise for improving predictions (Harrison et al, ; LaForgia et al, ; Prugh et al, ). Harrison et al () found a decline in mean community specific leaf area with drought.…”
Section: Discussionmentioning
confidence: 99%